I The Impact of Computational Thinking Skills on Mathematics Learning – Systematic Literature Review - Adi Janes Ngingi; Ariyadi Wijaya; Fitriana Yuli Saptaningtyas (Universitas Teknokrat Indonesia, 2026)
The demands of 21st-century education require students to possess higher-order thinking skills, with computational thinking (CT) being one of the core competencies. Although CT is crucial in helping students solve mathematical problems structurally, reality shows that students' CT skills remain moderate, and classroom instructions are predominantly procedural or rote-based. Objective:This study aims to systematically analyze and comprehensively map the impacts and research trends of integrating computational thinking into mathematics learning across various educational levels. Method: This study employed a Systematic Literature Review (SLR) method guided by the PRISMA framework. Literature searching was executed using the Scopus database, filtering for peer-reviewed journal articles, written in English or Indonesian, available in open-access format, and published between 2020 to 2028. Based on strict inclusion and exclusion criteria, the final selected articles were analyzed in-depth using bibliometric analysis and thematic synthesis. Results: The synthesis reveals that integrating CT into mathematics instructions yields significant positive impacts at elementary, junior, and senior high school levels. The core components of CT (decomposition, pattern recognition, abstraction, and algorithmic thinking) effectively enhance students' problem-solving capacities, logical reasoning, creativity, and learning motivation. Furthermore, the deployment of innovative approaches such as game-based learning, the 5E instructional model, TPACK, STEM, ethnomathematics, and digital tools (GeoGebra, Scratch, ChatGPT) consistently reinforces instructional efficacy. Nonetheless, critical challenges emerge, including variations in students' cognitive prior knowledge, constraints in assessment instruments, and teachers' misconceptions that narrow CT down strictly to computer programming or coding activities. Conclusion: The integration of CT serves as a vital bridge to transform mathematics pedagogy into a more explorative and meaningful experience, highlighting the urgent need for continuous teacher professional development and standardized CT assessment tools